MINAT BERKUNJUNG ULANG DAN WORD OF MOUTH PENGUNJUNG PADA DE TJOLOMADOE - Mahmudi Nur Arifin; M. Farid Wajdi; Kussudyarsana (Jurnal Cakrawala Ilmiah, 2023)
This study aims to determine the effect of responsibility (reliability), tangible (direct evidence), responsivenes (responsiveness), assurance (guarantee), empathy (empathy), tourist satisfaction on tourist satisfaction in de Tjolomadoe through visitor quality service as a mediating variable. The population in this study were de Tjolomadoe visitors who had visited. A sample search was carried out by distributing questionnaires online or offline in December 2021 and getting 180 respondents. After the selection was made, 100 samples were obtained that met the requirements and criteria in this study. Then data analysis was carried out using the Partial Least Square (PLS) – SEM approach with the help of SmartPLS version 3.0 software. The results of the study show that: (1) tangible has no significant effect on tourist satisfaction, so the first hypothesis is rejected. (2) reliability has no significant effect on tourist satisfaction, so the second hypothesis is rejected. Based on the results obtained reliability does not prove a positive influence on tourist satisfaction. (3) responsiveness has no significant effect on tourist satisfaction, so the third hypothesis is rejected. Based on the results obtained, responsiveness does not prove a positive influence on tourist satisfaction. (4) assurance has a significant effect on tourist satisfaction, so the fourth hypothesis is accepted. (5) empathy has a significant effect on tourist satisfaction, so that the fifth hypothesis is accepted. (6) tourist satisfaction has a significant effect on word of mouth, so that the sixth hypothesis is accepted. (6) tourist satisfaction has a significant effect on intention to revisit, so the seventh hypothesis is accepted. (7) Tourist satisfaction has a direct, positive and significant influence on the intention to revisit de Tjolomadoe tourists. (8) Tourist satisfaction does not mediate the direct effect of service quality on word of mouth tourists from de Tjolomadoe. (9) Tourist satisfaction does not mediate the direct effect of service quality on tourists' intention to revisit de Tjolomadoe